Nutritional (mineral content and antioxidant capacity) and organoleptic characterization of lettuce grown in soil amended with blood meal and its hydrolyzate - Victoria Fernández-Tucci; Ana Cervera-Mata; Alejandro Fernández-Arteaga; José Javier Quesada-Granados; María del Carmen Almécija-Rodríguez; Adriana Delgado-Osorio; Miguel Navarro-Moreno; Silvia Pastoriza; Gabriel Delgado; Miguel Navarro-Alarcón; José Ángel Rufián-Henares (Applied Food Research)
Hidden hunger is recognized as a global public health issue affecting especially at-risk population in developing countries. Food fortification is an effective tool to combat this problem. In this study, we investigated the re-use of blood meal (BM) and hydrolyzed blood meal (HBM) on Fe-Zn-Cu-Mn-Se levels, antioxidant capacity (AOC) and organoleptic characteristics of baby-lettuces. The experiment involved baby-lettuces’ cultivation on amended soils with BM and HBM in comparison to urea as control. Baby-lettuces without cultivation were also analyzed. Zn content significantly increased with both intervention treatments, while Mn and Se decreased (p < 0.001). Fe diminished with HBM application (p = 0.003). Baby-lettuces had significantly higher content for all minerals. AOC was mainly liberated during the in vitro fermentation process. BM and HBM impact positively on Zn content, without altering organoleptic perception, and total AOC measured by ABTS method in lettuce. Baby-lettuces are important sources for Fe-Cu-Mn in diet.